PENDAFTARAN ANAK LUAR KAWIN DI KOTA MEDAN (STUDI DINAS KEPENDUDUKAN DAN CATATAN SIPIL) - MINANTY GABY TAMARA SIBARANI (PREMISE LAW JURNAL, 2017)
Birth is a juristic fact which causes legal consequence since it is related to inheritance, family relationship, and the other relationships concerning the birth of a new subject. A legitimate marriage will yield a legitimate child that is legal before law, while a child who is born from an illegitimate marriage will be considered as an illegitimate child. The objective if the research was to find out the regulation on illegitimate child in the Indonesian positive law, the procedure of registering an illegitimate child in the Residential Affairs and Civil Registry Office in Medan, and the legal consequence of registering an illegitimate child in the Residential Affairs and Civil Registry Office in Medan. The result of the research showed that the regulation of illegitimate child in the Indonesian Positive Law is regulated in the Civil Code and Law No. 1/1974 on Marriage and in the Islamic Laws. According to the Civil Law, an illegitimate child has to be registered so that he will have the same right as the legitimate one Keywords: Registration, Illegitimate Child, Civil Registry